Pengembangan Pakan Ikan untuk Menekan Biaya Produksi Budidaya Lele - Rusnandari Retno Cahyani; Anniez Rachmawati Musliffah (Jurnal Pengabdian Pada Masyarakat, 2018)
DEVELOPING IN FISH FEED FOR SAVING PRODUCTION COSTS OF CATFISH CULTIVATION. Making catfish feed from waste raw materials and the surrounding environment in order to save production cost. The growth of fish depends on the feed intake, but this is not sufficiently well due to the increase in feed prices. Therefore, it is necessary to innovate the production of feed that utilizes the natural resources around the surrounding waste. Development of fish feed to reduce costs by 4 ways i.e. fish feed with organic fertilization, utilization of Azzola plants or mini water spikes, organic feed from growing and the surrounding waste and artificial pellet feed with appropriate technology. Feeding innovation is expected to reduce the production cost of 70% which designate is feed. This devotion partner is a group of Mulyo Tani 1 and Orphanage group of orphanage son of Muhammadiyah Setrorejo, Baturetno. This devotion activity successfully developed catfish farming business by doing continuous feed development.